1995
DOI: 10.1590/s0004-282x1995000100002
|View full text |Cite
|
Sign up to set email alerts
|

Distúrbios cognitivos na doença de Parkinson: correlações eletrencefalográficas

Abstract: RESUMO -62 pacientes com diagnóstico de doença de Parkinson idiopática e 30 pacientes controle foram avaliados quanto a distúrbios mnemônicos e psíquicos, utilizando-se os critérios do DSM III-R, o mini-mental e a escala de Hamilton para depressão. Todos foram submetidos a eletrencefalograma (EEG) com fotoestimulação intermitente. Dos pacientes parkinsonianos, 24,2% apresentavam depressão psíquica, 14,5% ansiedade, 12,9% distimia, 3,2% demência e 45,2% não apresentavam quaisquer alterações de acordo com os cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…In the present PD study, the finding of cognitive changes in 53% of the cases, of which 22% of the individuals had dementia and 31% mild cognitive impairment, was within the ranges of prevalence found in the literature. 2,21 The PD patients showed greater slowing down on the qEEG as compared to healthy individuals in a way similar to other studies, 8 10 and an association was shown between this increase in amplitudes in the slow ranges and the occurrence of dementia. 3,4,6,22…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present PD study, the finding of cognitive changes in 53% of the cases, of which 22% of the individuals had dementia and 31% mild cognitive impairment, was within the ranges of prevalence found in the literature. 2,21 The PD patients showed greater slowing down on the qEEG as compared to healthy individuals in a way similar to other studies, 8 10 and an association was shown between this increase in amplitudes in the slow ranges and the occurrence of dementia. 3,4,6,22…”
Section: Discussionsupporting
confidence: 88%
“…2 7 Initial evaluations in patients with PD using the EEG showed a slowing of the basal rhythm in the posterior regions, associated with an increase in diffuse theta activity, or even slow, intermittent focal waves. 8,9 An increase in slow activities was also reported using the quantitative EEG (qEEG). 4,6,10 These alterations in the EEG and qEEG only occurred in PD patients with associated dementia.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, a prominent posterior slow-wave EEG activity with periodic fluctuations in the pre-alpha/theta range is a supportive biomarker for DLB diagnosis 56 . Some Brazilian studies have investigated the quantitative EEG changes concerning cognitive decline in PD patients, showing increased posterior theta and delta amplitude in patients with MCI-PD or PDD 57 ),( 58 and differences in EEG power and coherence in AD and PDD 59 ),( 60 .…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, atividade no eletroencefalograma (EEG) de onda lenta posterior proeminente com flutuações periódicas na faixa pré-alfa / teta constitui um biomarcador de suporte no diagnóstico de DCL, sendo útil na distinção entre DCL e DA 56,57 . Estudos prévios com coortes brasileiras investigaram as mudanças quantitativas no EEG relacionadas ao declínio cognitivo em pacientes com DP, e encontraram amplitude posterior teta e delta aumentada em pacientes com CCL por DP ou DDP 57,58 , assim como diferenças no padrão do EEG entre DA e DDP 59,60 .…”
Section: Estudounclassified
“…Furthermore, a prominent posterior slow-wave EEG activity with periodic fluctuations in the pre-alpha/theta range is a supportive biomarker for DLB diagnosis 56 . Some Brazilian studies have investigated the quantitative EEG changes concerning cognitive decline in PD patients, showing increased posterior theta and delta amplitude in patients with MCI-PD or PDD 57,58 and differences in EEG power and coherence in AD and PDD 59,60 .…”
Section: Ancillary Investigation and Biomarkersmentioning
confidence: 99%